The 'augmented' circles: A video-guided solution for the down-the-beam positioning of im nail holes - Londei, Roberto; Esposito, Marco; Diotte, Benoit; Weidert, Simon; Euler, Ekkehard; Thaller, Peter; Navab, Nassir; Fallavollita, Pascal (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2014)
Intramedullary nailing is the surgical procedure mostly used in fracture reduction of the tibial and femoral shafts. Following successful insertion of the nail into the medullary canal, it must be fixed by inserting screws through its proximal and distal locking holes. Prior to distal locking of the nail, surgeons must position the C-arm device and patient leg in such a way that the nail holes appear as circles in the X-ray image. This is considered a 'trial and error' process, is time consuming and requires many X-ray shots. We propose an augmented reality application that visually depicts to the surgeon two 'augmented' circles, their centers lying on the axis of the nail hole, making it visible in space. After an initial X-ray image acquisition, real-time video guidance allows the surgeon to superimpose the 'augmented' circles by moving the patient leg; the result being nail holes appearing as circles. Our nail pose recovery was evaluated on 1000 random trials and we consistently recovered the nail angulation within 2.76 ± 1.66°. Lastly, in a preclinical experiment involving 7 clinicians, we demonstrated that in over 95% of the trials, the nail hole appeared as a circle using an initial X-ray image. © 2014 Springer International Publishing Switzerland.
CRIS-Team Scopus Importer:2023-03-08
Keywords: down-the-beam positioning; freehand distal locking; interlocking of intramedullary nailing; medical augmented reality; orthopedic and trauma surgery; visualization